2021
DOI: 10.1002/asjc.2711
|View full text |Cite
|
Sign up to set email alerts
|

L2‐gain robust trajectory tracking control for quadrotor UAV with unknown disturbance

Abstract: In this paper, the trajectory tracking problem of the position and yaw angle of an underactuated quadrotor UAV is studied. Considering that the quadrotor UAV often encounters unknown disturbance resulted by model parameter perturbations and environmental changes, a new L 2 -gain robust control method is presented based on dissipation theory. First, the dynamic model of the quadrotor UAV with disturbances is transformed by introducing three virtual control variables. In this way, the trajectory tracking control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…For each UAV, the observer is designed with local information and its neighbor; thus, the observers are distributed. The observers (8)- (11) have the properties described in the following theorem. Theorem 3.1.…”
Section: ̂ 𝜌 I Vimentioning
confidence: 99%
See 2 more Smart Citations
“…For each UAV, the observer is designed with local information and its neighbor; thus, the observers are distributed. The observers (8)- (11) have the properties described in the following theorem. Theorem 3.1.…”
Section: ̂ 𝜌 I Vimentioning
confidence: 99%
“…Theorem 3.1. Consider the distributed observers ( 8)- (11). For any initial states ρi (t 0 ), vi (t 0 ),…”
Section: ̂ 𝜌 I Vimentioning
confidence: 99%
See 1 more Smart Citation
“…In a UAV swarm, there are frequent and sudden shifts between favorable and unfavorable states in a complex battlefield. These shifts can be triggered by external, internal, or human-induced disruptions, resulting in crashed drones, loss of communication links, or diminished communication capabilitie [1,8]. Based on simulation results, Xu observed that the duration of the recovery phase becomes prolonged as the proportion of failed agents increases.…”
Section: They Ingeniously Combined Internet Of Things Technologiesmentioning
confidence: 99%